2011
DOI: 10.1002/crat.201100494
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of Czochralski growth of quadratic silicon crystals by means of a travelling magnetic field

Abstract: We present 3D simulations of melt flow in a Czochralski process of Si single crystal growth with a travelling magnetic field (TMF). The choice of the TMF significantly influences the thermal field in the melt. Using a downwards TMF field the induced convection causes a thermal field with a low radial component of the temperature gradient along the melt surface and a high vertical component below the crystal. Such a thermal field allows the kinetics‐based creation of {110} side facets, which was proven in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Therefore, to obtain large square Si single bulk crystals with a large side-face width, it is important to develop a technology to maintain a small radial temperature gradient near the growth interface even when the supercooling in the melt increases. This concept appears to be consistent with that of Miller et al 13) In the present method, the radial temperature gradient near the growing interface is proportional to ¦T in . Therefore, to obtain large square Si single bulk crystals with a large side-face width, it is important to keep ¦T in small even when the low-temperature region becomes larger.…”
Section: Side-face Width (Cm)supporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, to obtain large square Si single bulk crystals with a large side-face width, it is important to develop a technology to maintain a small radial temperature gradient near the growth interface even when the supercooling in the melt increases. This concept appears to be consistent with that of Miller et al 13) In the present method, the radial temperature gradient near the growing interface is proportional to ¦T in . Therefore, to obtain large square Si single bulk crystals with a large side-face width, it is important to keep ¦T in small even when the low-temperature region becomes larger.…”
Section: Side-face Width (Cm)supporting
confidence: 92%
“…It was reported that the supercooling of the Si melt in the radial direction of an ingot and a low radial temperature gradient are important factors in obtaining Si single bulk crystals with a square top face. [10][11][12][13] The size of the square face is determined by the side-face width of the four-cornered pattern on the top surface of the ingot. Figure 6 shows the side-face widths (cm) of several bulk crystals grown by the present method as a function of 1/¦T in (K ¹1 ).…”
Section: Factors Affecting Growth Of Square Si Single Bulk Crystalsmentioning
confidence: 99%
See 3 more Smart Citations